OPTIMALISASI STRATEGI PEMASARAN UNTUK MEMPERKUAT DAYA SAING PANTAI GEGER SEBAGAI DESTINASI WISATA DI BADUNG (Jurnal Destinasi Pariwisata, 2026)
This study aims to optimize marketing strategies to strengthen the competitiveness of Geger Beach as a marine tourism destination in Badung. Geger Beach, as a tourist destination in Bali, has superior marine tourism potential, but faces various marketing obstacles that affect its effectiveness. The research method used is qualitative data with supporting quantitative data, along with data collection techniques through observation, interviews, and questionnaires. Analysis was conducted using SWOT and VRIO to identify strengths, weaknesses, opportunities, and threats, while assessing the destination's resources and capabilities. The results revealed that optimizing marketing strategies, including product, price, place, promotion, human resources, processes, and physical evidence, can increase the competitiveness of Geger Beach. Recommendations are provided to address inhibiting factors and improve the marketing effectiveness of this marine tourism destination to become more competitive in both national and international tourism markets